Eight new species of the genus Siccia Walker from mainland Africa (Lepidoptera: Erebidae: Arctiinae: Lithosiini) - Volynkin, Anton V.; Saldaitis, Aidas; Müller, Günter C. (Zootaxa, 2025)
Eight new species of the genus Siccia Walker, 1854 are described from mainland Africa: Siccia bomassa Volynkin, sp. nov. (Republic of Congo), Siccia campo Volynkin, sp. nov. (Cameroon), Siccia haynesi Volynkin, sp. nov. (Zimbabwe), Siccia makao Volynkin, sp. nov. (Republic of Congo), Siccia mondika Volynkin, sp. nov. (Republic of Congo), Siccia odzala Volynkin, sp. nov. (Republic of Congo), Siccia salonga Volynkin, Saldaitis & Müller, sp. nov. (Democratic Republic of Congo), and Siccia taita Volynkin, sp. nov. (Kenya). Adults and male and female genitalia of the new and similar species are illustrated.